Endometrial and Menstrual Blood Mesenchymal Stem/Stromal Cells: Biological Properties and Clinical Application - Bozorgmehr, Mahmood; Gurung, Shanti; Darzi, Saeedeh; Nikoo, Shohreh; Kazemnejad, Somaieh; Zarnani, Amir-Hassan; Gargett, Caroline E. (Frontiers in Cell and Developmental Biology, 2020)
A highly proliferative mesenchymal stem/stromal cell (MSC) population was recently discovered in the dynamic, cyclically regenerating human endometrium as clonogenic stromal cells that fulfilled the International Society for Cellular Therapy (ISCT) criteria. Specific surface markers enriching for clonogenic endometrial MSC (eMSCs), CD140b andCD146 co-expression, and the single marker SUSD2, showed their perivascular identity in the endometrium, including the layer which sheds during menstruation. Indeed, cells with MSC properties have been identified in menstrual fluid and commonly termed menstrual blood stem/stromal cells (MenSCs). MenSCs are generally retrieved from menstrual fluid as plastic adherent cells, similar to bone marrow MSCs (bmMSCs). While eMSCs and MenSCs share several biological features with bmMSCs, they also show some differences in immunophenotype, proliferation and differentiation capacities. Here we review the phenotype and functions of eMSCs and MenSCs, with a focus on recent studies. Similar to other MSCs, eMSCs and MenSCs exert immunomodulatory and anti-inflammatory impacts on key cells of the innate and adaptive immune system. These include macrophages, T cells and NK cells, both in vitro and in small and large animal models. These properties suggest eMSCs and MenSCs as additional sources of MSC for cell therapies in regenerative medicine as well as immune-mediated disorders and inflammatory diseases. Their easy acquisition via an office-based biopsy or collected from menstrual effluent makes eMSCs and MenSCs attractive sources of MSCs for clinical applications. In preparation for clinical translation, a serum-free culture protocol was established for eMSCs which includes a small molecule TGFβ receptor inhibitor that prevents spontaneous differentiation, apoptosis, senescence, maintains the clonogenic SUSD2+ population and enhances their potency, suggesting potential for cell-therapies and regenerative medicine. However, standardization of MenSC isolation protocols and culture conditions are major issues requiring further research to maximise their potential for clinical application. Future research will also address crucial safety aspects of eMSCs and MenSCs to ensure these protocols produce cell products free from tumorigenicity and toxicity. Although a wealth of data on the biological properties of eMSCs and MenSCs has recently been published, it will be important to address their mechanism of action in preclinical models of human disease.